Epoxy resin/cyanate ester composites containing DOPO and wollastonite with simultaneously improved flame retardancy and thermal resistance. (August 2020) - Wang, Zhengzhou; Gao, Xin; Li, Wenfeng
Flame-retardant epoxy (EP) resin/cyanate ester (CE) composites were prepared with 9, 10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) and wollastonite (Wo). The combustion behavior of the flame-retardant EP/CE composites was investigated by limiting oxygen index (LOI), UL-94, and cone calorimeter tests. It is found that the EP/CE composite containing 7 wt% DOPO and 3 wt% Wo (sample 7DO/3Wo/EP/CE) exerts the best flame retardancy (LOI 35.5% and UL-94 V-0 rating). The peak heat release rate and total heat release of sample 7DO/3Wo/EP/CE increase slightly, while total smoke release decreases about 14% compared with the EP/CE composite containing 10 wt% DOPO (sample 10DO/EP/CE). Thermal studies indicate that the glass transition temperature and temperature at 5% mass loss of sample 7DO/3Wo/EP/CE are higher than that of sample 10DO/EP/CE. Moreover, the mechanical properties of EP/CE composites were investigated.